# Subtract the first rational number from the second in each of the following:(i) $\frac{3}{8}, \frac{5}{8}$(ii) $\frac{-7}{9}, \frac{4}{9}$(iii) $\frac{-2}{11}, \frac{-9}{11}$(iv) $\frac{11}{13}, \frac{-4}{13}$(v) $\frac{1}{4}, \frac{-3}{8}$(vi) $\frac{-2}{3}, \frac{5}{6}$(vii) $\frac{-6}{7}, \frac{-13}{14}$(viii) $\frac{-8}{33}, \frac{-7}{22}$

To do:

We have to subtract the first rational number from the second.

Solution:

We know that,

$(-) \times(-)=(+)$

Therefore,

(i) Subtracting $\frac{3}{8}$ from $\frac{5}{8}$, we get,

$\frac{5}{8}-\frac{3}{8}=\frac{5-3}{8}$

$=\frac{2}{8}$

$=\frac{1}{4}$

(ii) Subtracting $\frac{-7}{9}$ from $\frac{4}{9}$, we get,

$\frac{4}{9}-(\frac{-7}{9})=\frac{4}{9}+\frac{7}{9}$

$=\frac{4+7}{9}$

$=\frac{11}{9}$

(iii) Subtracting $\frac{-2}{11}$ from $\frac{-9}{11}$, we get,

$\frac{-9}{11}-(\frac{-2}{11})=\frac{-9}{11}+\frac{2}{11}$

$=\frac{-9+2}{11}$

$=\frac{-7}{11}$

(iv) Subtracting $\frac{11}{13}$ from $\frac{-4}{13}$, we get,

$\frac{-4}{13}-\frac{11}{13}=\frac{-4-11}{13}$

$=\frac{-15}{13}$

(v) Subtracting $\frac{1}{4}$ from $\frac{-3}{8}$, we get,

$\frac{-3}{8}-(\frac{1}{4})=\frac{-3}{8}-\frac{1}{4}$

$=\frac{-3-2}{8}$

$=\frac{-5}{8}$

(vi) Subtracting $\frac{-2}{3}$ from $\frac{5}{6}$, we get,

$\frac{5}{6}-(\frac{-2}{3})=\frac{5}{6}+\frac{2}{3}$

$=\frac{5+2\times2}{6}$

$=\frac{5+4}{6}$

$=\frac{9}{6}$

$=\frac{3}{2}$

(vii) Subtracting $\frac{-6}{7}$ from $\frac{-13}{14}$, we get,

$\frac{-13}{14}-(\frac{-6}{7})=\frac{-13}{14}+\frac{6}{7}$

$=\frac{-13+6\times2}{14}$

$=\frac{-13+12}{14}$

$=\frac{-1}{14}$

(viii) Subtracting $\frac{-8}{33}$ from $\frac{-7}{22}$, we get,

$\frac{-7}{22}-(\frac{-8}{33})=\frac{-7}{22}+\frac{8}{33}$

$=\frac{-7\times3+8\times2}{66}$

$=\frac{-21+16}{66}$

$=\frac{-5}{66}$

Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

21 Views